EDUCATION AND TRAINING CENTER OF BASKETBALL IN SALATIGA WITH A SUSTAINABLE ARCHITECTURE DESIGN - Syamsul Karim (Architecture Study Program, Department of Civil Engineering, Faculty of Engineering, Universitas Negeri Semarang, Indonesia, 2023)
Basketball has become one of the sports that is highly favored by people worldwide, including in Indonesia. In Indonesia itself, there is a premier national competition known as the Indonesian Basketball League (IBL), which is participated in by numerous major cities, including Salatiga. Salatiga possesses great potential for the development of basketball in Indonesia. The city's numerous championship victories and individual accolades bestowed upon Salatiga basketball athletes highlight its significant contribution to the advancement of basketball in the country. However, in order to further support and nurture these achievements and potentials, it is essential to provide adequate facilities capable of accommodating the needs of athletes, aspiring athletes, and basketball enthusiasts throughout Indonesia, particularly in Salatiga. Establishing an internationally standardized facility with a focus on education and training would serve as a medium to prepare future athletes. The primary objective of this design report is to outline the plans for the Salatiga Basketball Education and Development Center, utilizing a Sustainable Architecture approach, which would effectively cater to the requirements of athletes and aspiring athletes in enhancing their knowledge and basketball skills. Additionally, this planning aims to fulfill the building's function as a competitive venue for national athletes participating in events held in Salatiga. The design of the basketball education and development center entails various processes, including problem identification, data collection, site identification, site selection, site analysis, and the implementation of the sustainable architecture approach.